THE ONE UNCOMMON CASE OF BRUCELLOSIS MENINGOENCEPHALITIS - A. M. Gusniev; N. S. Karnaeva; S. G. Agaeva (LLC "Diagnostics and Vaccines", 2015)
Nowadays, a rare case of brucellosis meningoencephalitis is presented. Indicated on the features of its clinical course, the various laboratory analyzes are adduced and the methods of rational therapy are discussed.